Fatores associados a não efetivação da alta na atenção domiciliar para a atenção primária à saúde - Erika Guimaraes Lage (2018)
Introduction: Home Care consists of a health care integrated into the Health Care Network , characterized by a set of preventive, treatment, rehabilitation, palliation and health promotion actions provided at home, guaranteeing the continuity of the assistance to people who require clinical care, but without the need for hospitalization. The process of integrating Home Care Service with other services and particularly with Primary Health Care (PHC) reveals difficulties, especially those related to the mechanisms of entry and continuity of PHC care after discharge from Home Care Service , and studies are still scarce related to such limitations. Method: Epidemiological study of a cross - sectional design, carried out in 2017, based on an Home Care Service of the metropolitan region of the State - Minas Gerais - Brazil. Data are secondary to medical records and database of 157 users served by Multiprofessional Home Care Clinical Teams in 2016, including those assisted in 2016 remaining in 2017 until the collection period. Sociodemographic and economic characteristics, health, behavioral and access to the Home Care Service of the users, as well as sociodemographic characteristics of their caregivers, were analyzed. The analysis was carried out by the Stata program, version 14.0, using the logistic regression to determine the factors associated with non-effective discharge from SAD to PHC. Outcome: Among the users investigated, 22.29% did not register discharge for PHC. It was observed that the increase in the age and the frequency of visits received by the user were associated with the non-effectiveness of the users' discharge. In addition, having an income higher than 3 minimum wages increased (2.55 times) the prevalence of noneffective increase of Home Care Service users to PHC compared to lower income users (up to 1 minimum wage). Being from the Emergency care unit, in turn, decreased the prevalence of non-effectiveness of the users' discharge - when controlled by the other variables present in the model. Conclusion: With the result of this study, it is possible to perceive the existence of a group of users in whom Home Care Service has difficulties in effecting the discharge to APS, being the discharge also related to the type of access to the service. Although in its results it was not possible to identify the temporality of the associations shown in the result, because it is a cross-sectional study, this work advances in the perspective of new epidemiological information and the analysis of data not yet fully explored on home care